Comparison between Communication Technology used in Smart Building - Syarmila Bt Sameon S.; Yussof S.; Jorgensen B.N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Air conditioning; Automation; Wireless sensor networks; Appropriate technologies; Automated process; Communication technologies; Communications technology; Construction of buildings; ITS applications; Quality of life; Supervisory control systems; Intelligent buildings